The effect of spending cuts on teen pregnancy - Paton, David; Wright, Liam (Elsevier, 2017)
In recent years, English local authorities have been forced to make significant cuts to devolved expenditure. In this paper, we examine the impact of reductions in local expenditure on one particular public health target: reducing rates of teen pregnancy. Contrary to predictions made at the time of the cuts, panel data estimates provide no evidence that areas which reduced expenditure the most have experienced relative increases in teenage pregnancy rates. Rather, expenditure cuts are associated with small reductions in teen pregnancy rates, a result which is robust to a number of alternative specifications and tests for causality. Underlying socio-economic factors such as education outcomes and alcohol consumption are found to be significant predictors of teen pregnancy.